Imino‐λ3‐iodane and Catalytic Amount of I2‐Mediated Synthesis of N‐Allylsulfenamides via [2, 3]‐Sigmatropic Rearrangement. Issue 41 (20th October 2020) - Makitalo, Cody L.; Yoshimura, Akira; Rohde, Gregory T.; Mironova, Irina A.; Yusubova, Rosa Y.; Yusubov, Mekhman S.; Zhdankin, Viktor V.; Saito, Akio
Abstract : A facile metal‐free [2, 3]‐sigmatropic rearrangement reaction of allyl sulfides via N ‐sulfilimine intermediates has been developed. Treatment of allyl sulfides with imino‐λ 3 ‐iodanes in the presence of a catalytic amount of elemental iodine allowed the reaction to proceed under mild conditions and gave the corresponding N ‐allylsulfenamide compounds in moderate to good yields. Several N ‐allylsulfenamide structures have been confirmed by single‐crystal X‐ray crystallography. The reaction initially involves the sulfonylimino group transfer reaction between imino‐λ 3 ‐iodane and the sulfur atom, resulting in the formation of N ‐sulfilimine species, followed by [2, 3]‐sigmatropic rearrangement to form the N ‐allylsulfenamide. Abstract : Imino‐λ 3 ‐iodane and catalytic I2 ‐mediated facile metal‐free [2, 3]‐sigmatropic rearrangement reaction of allyl sulfides producing N ‐allysulfenamiides has been developed